Communication of Caregivers and Santri at Islamic Boarding Schools in a Gender Perspective - Linda Nur Wahyuningsih; Rio Febriannur Rachman (Kanal: Jurnal Ilmu Komunikasi, 2020)
This strudy aim is to describe how the interaction between caregivers and students, both men and women, in Islamic boarding schools, as religious-based educational institutions. The location of the study is Bustanul Ulum Islamic boarding schools, Sawaran Kulon, Kedungjajang, Lumajang. This study uses qualitative method, through the phenomenological approach, which is introduced by Lanigan. Lanigan argued, the communication process has a correlation with the residence of communicator and the communicant. In the context of this study, the residence is the Islamic boarding school, while communicators and communicants are caregivers and students. Sources of research data obtained through observing and interviewing, and reading literature regarding the research topic. Observations carried out for ten days (March 15, 2020 until March 25, 2020). Interviews are conducted with caregivers and students. The results are, first; communication between caregivers and students in Bustanul Ulum Islamic boarding schools runs both verbally and non-verbally. In general, caregivers play a more communicator role, and santri become communicants. Second; communication carried out across gender. Only indeed, interactions and communication between Kiai and female santri are not as close and frequent as interactions and communication between Kiai and male santri. Likewise, interactions and communication between Nyai and male santri are not as close and frequent as Nyai and female santri interactions and communication. Because in the curriculum or rules that have been set, the who focuses of intensive teaching of male students, is the Kiai. While the one who focuses intensively in teaching female students, is Nyai.